2008
DOI: 10.1590/s0034-72992008000600010
|View full text |Cite
|
Sign up to set email alerts
|

Interação entre grau de perda auditiva e o incômodo com zumbidos em trabalhadores com história de exposição ao ruído

Abstract: Heari ng loss and tinnitus impact the lives of workers in every instance of their lives. Aim: this paper aims to investigate the existence of a dose-response relationship between hearing loss and tinnitus by determining whether higher levels of hearing loss can be associated with increased tinnitus-related discomfort. Materials and method: this cross-sectional case study assessed 284 workers exposed to occupational noise through pure tone audiometry. Test results were categorized as defined by Merluzzi. Indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
1
4
0
4
Order By: Relevance
“…The Hearing Loss factor has low impact (-0.007) on the use of PPE. Similar results were achieved by Cavalli et al (2004) and Dias & Cordeiro (2008). Thus, it is confirmed that the existence of losses already constituted is not reflected in greater use of the equipment.…”
Section: C) Hearing Losssupporting
confidence: 84%
“…The Hearing Loss factor has low impact (-0.007) on the use of PPE. Similar results were achieved by Cavalli et al (2004) and Dias & Cordeiro (2008). Thus, it is confirmed that the existence of losses already constituted is not reflected in greater use of the equipment.…”
Section: C) Hearing Losssupporting
confidence: 84%
“…Of the 49 workers surveyed, only five (10.2%) reported tinnitus, and there was no statistically significant difference between tinnitus and no emissions. In contrast, in the literature, there is a high prevalence of tinnitus in the population exposed to occupational noise (17,18).…”
Section: Discussionmentioning
confidence: 95%
“…Tinnitus is a symptom that often accompanies occupational hearing loss 26 , difficulties in being able to provide out of work contexts and negative influence on the quality of life of workers and the people who surround 27,28 . While none of the candidates analyzed have complained of tinnitus, this symptom should not be disregarded because to discard it, one should first examine the complaints of a larger population of workers exposed to noise and with more than five years of exposure.…”
Section: Discussionmentioning
confidence: 99%